Generational perspective on asthma self‐management in the Bangladeshi and Pakistani community in the United Kingdom: A qualitative study. (23rd August 2022) - Ahmed, Salina; Pinnock, Hilary; Dowrick, Anna; Steed, Liz
Abstract: Background: Self‐management strategies improve asthma outcomes, although interventions for South Asian populations have been less effective than in White populations. Both self‐management and culture are dynamic, and factors such as acculturation and generation have not always been adequately reflected in existing cultural interventions. We aimed to explore the perspectives of Bangladeshi and Pakistani people in the United Kingdom, across multiple generations (first, second and third/fourth), on how they self‐manage their asthma, with a view to suggesting recommendations for cultural interventions. Methods: We purposively recruited Bangladeshi and Pakistani participants, with an active diagnosis of asthma from healthcare settings. Semi‐structured interviews in the participants' choice of language (English, Sylheti, Standard Bengali or Urdu) were conducted, and data were analysed thematically. Results: Twenty‐seven participants (13 Bangladeshi and 14 Pakistani) were interviewed. There were generational differences in self‐management, influenced by complex cultural processes experienced by South Asians as part of being an ethnic minority group. Individuals from the first generation used self‐management strategies congruent to traditional beliefs such as 'sweating' and often chose to travel to South Asian countries. Generations born and raised in the United Kingdom learnt and experimented with self‐management based on their fused identities and modified their approach depending on whether they were in familial or peer settings. Acculturative stress, which was typically higher in first generations who had migration‐related stressors, influenced the priority given to asthma self‐management throughout generations. The amount and type of available asthma information as well as social discussions within the community and with healthcare professionals also shaped asthma self‐management. Conclusions: Recognizing cultural diversity and its influence of asthma self‐management can help develop effective interventions tailored to the lives of South Asian people. Patient or Public Contribution: Patient and Public Involvement colleagues were consulted throughout to ensure that the study and its materials were fit for purpose.